Official Tourism Websites of ASEAN Countries: A Linguistic Strategies Analysis - Kunghair, Suna (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2025)
The official tourism websites of ASEAN countries functioned as essential tools for drawing international visitors because they played a vital economic role in these nations. This research investigated the official tourism websites of Indonesia, Malaysia, Singapore, and Thailand to analyze their linguistic strategies for informative, persuasive, and interactional meta‑discourse elements. The study analyzed tourism discourse through Hyland’s (2005) Meta‑Discourse Framework by conducting qualitative discourse analysis of hedges, boosters, attitude markers, engagement markers, and self‑mentions. The findings showed that Indonesia and Malaysia employed detailed descriptions and sensory language to attract tourists, emphasizing informative and persuasive strategies. In contrast, Singapore and Thailand used interactional meta‑discourse, particularly hedges and boosters to create credibility and sustain visitor engagement. The research demonstrated how ASEAN nations tailored their linguistic approaches to build destination branding while reaching potential visitors and establishing credibility. It also revealed that digital tourism promotion became more effective through strategic language optimization, interactive features, and personalized content. Ultimately, the study contributed to tourism discourse analysis by illustrating how ASEAN nations successfully marketed their destinations using targeted language strategies.